Cleaning of niobium surface by plasma of diffuse discharge at atmospheric pressure; Journal of Physics: Conference Series; Vol. 869 : Frontiers in Theoretical and Applied Physics/UAE 2017 (FTAPS 2017) - Tarasenko V. F. Victor Fedotovich; Erofeev M. V. Mikhail Vladimirovich; Shulepov M. A. Mikhail A.; Ripenko V. S. (2017, 2017)
Title screen